Energy shifts of heavy and light holes and electroluminescence intensity increase in p-AlxGa1-xAs/GaAs1-yPy/n-AlxGa1-xAs laser diode heterostructure under uniaxial compression - Bogdanov, E. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)
Numerical calculations of the valence band and conduction band size quantized levels in a strained p-AlxGa1-xAs/GaAs1-yPy/n-AlxGa1-xAs (y = 0.16) double heterostructure were performed for different values of the external uniaxial compression along the [110] direction. They indicate that the two upper levels in the valence band—light hole LH1 and heavy hole HH1—intersect at a pressure of about 4 kbar, and a strong LH1-HH1 state mixing develops around the crossover point. The results of calculations explain the nonlinear character of the photon energy shift and electroluminescence intensity increase that were experimentally observed in these structures